2011
DOI: 10.1016/j.juro.2011.01.074
|View full text |Cite
|
Sign up to set email alerts
|

Update on AUA Guideline on the Management of Benign Prostatic Hyperplasia

Abstract: New pharmacotherapies and technologies have emerged which have impacted treatment algorithms. The management of LUTS/BPH continues to evolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
851
0
33

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,202 publications
(896 citation statements)
references
References 37 publications
12
851
0
33
Order By: Relevance
“…Bei Symptomen die auf eine Pathologie der Prostata hinweisen ist gegebenenfalls eine PSA Wert-Bestimmung zu empfehlen [47][48][49]. Eine Kontrolle der Nierenretentionsparameter ist gegebenenfalls bei einer Überlaufinkontinenz durchzuführen.…”
Section: Blutanalyseunclassified
“…Bei Symptomen die auf eine Pathologie der Prostata hinweisen ist gegebenenfalls eine PSA Wert-Bestimmung zu empfehlen [47][48][49]. Eine Kontrolle der Nierenretentionsparameter ist gegebenenfalls bei einer Überlaufinkontinenz durchzuführen.…”
Section: Blutanalyseunclassified
“…Evidence suggests that HoLEP provides superior outcomes compared to TURP and open simple prostatectomy in men with BPH, regardless of prostate size [2][3][4][5] . Additionally, a recent study found that HoLEP is associated with decreased hospital costs compared to open prostatectomy.…”
Section: Introductionmentioning
confidence: 99%
“…The latest version of the guidelines on the management of BPH from the American Urological Association [4] and the guidelines on the management of male LUTS from the European Urological Association [5] refer to alfuzosin, doxazosin, tamsulosin and terazosin, while the Japanese guidelines for BPH also recommend naftopidil and silodosin [6] . The reports submitted to the US Food and Drug Administration Adverse Event Reporting System between 1997 and 2011 assessed the safety profiles of alfuzosin, doxazosin, tamsulosin, terazosin, naftopidil, silodosin and urapidil [7] .…”
Section: Introductionmentioning
confidence: 99%